Pengaruh Strategi Pembelajaran dan Motivasi Belajar terhadap Hasil Belajar Bahasa Indonesia Peserta Didik Kelas IX SMP Tarakanita 4 Jakarta - Cicilia Setyowati; Hartati Mucthar; Robinson Situmorang (Jurnal Ilmiah Wahana Pendidikan, 2018)
This research has a purpose to determine the effect of learning strategies and learning motivation on the results of grade IX Indonesian language learning. This research was carried out at Jakarta Tarakanita 4 Middle School. The research uses an experimental research of design treatment by level 2 x 2 with 28 students as a sample which is taken by simple random sampling at Jakarta Tarakanita 4 Middle School. The results showed that: (1) the results of learning Indonesian for class IX students of Jakarta Tarakanita 4 Junior High School who followed the learning process using contextual learning strategies were higher than students who followed the learning process using expository learning strategies, (2) there the effect of interaction between learning strategies and motivation on the learning outcomes of Indonesian students, (3) the results of learning Indonesian for students who follow the learning process by using contextual learning strategies with high motivation results are higher than students who follow the learning process using learning strategies expository with high motivation, (4) Indonesian language learning outcomes for students who follow the learning process using contextual learning strategies with low motivation are the same results as students who follow the learning process by using expository learning strategies with low motivation.